Ants and their effects on an insect herbivore community associated with the inflorescences of Byrsonima crassifolia (Linnaeus) H.B.K. (Malpighiaceae) - Fernandes,G. Wilson (2005)
The effects of ants on the insect community on inflorescences of Byrsonima crassifolia (Malpighiaceae) were tested in an ant exclusion experiment in a cerrado vegetation in southeastern Brazil. Forty-four species of insects (23 families) and nine species of ants (6 genera and 3 subfamilies) were found on the inflorescences of B. crassifolia. The exclusion of ants, primarily Camponotus sericeiventris and Camponotus spp., reduced the treehopper population to 20% of the original abundance. Ant exclusion and time influenced the abundance of chewing (Exclusion, P<0.001; Time, P<0.002), and sucking insects (Exclusion, P<0.02; Time, P<0.01). Twice as many chewing and sucking insects were found on ant-excluded inflorescences as compared to control inflorescences (P<0.001). One and half more sucking insects were found on ant-excluded than on control inflorescences. Only time significantly influenced the richness of chewing and sucking insects associated with B. crassifolia inflorescences. Inflorescences on control branches were significantly less attacked by herbivores than inflorescences on ant-excluded branches (P<0.001). Therefore, these results suggest that the presence of ants alters the structure of insect herbivore community associated with B. crassifolia.